Skills assistance to families and cadres in the management of hypertension In the elderly in Ladang Baro Village, Meukek District, South Aceh Regency - Syam Irwan; Cut Rahmi; Rasima Rasima (CV. AFDIFAL MAJU BERKAH, 2024)
Hypertension is an abnormal increase in systolic pressure of 140 mmHg or more and diastolic pressure of 120 mmHg. In Indonesia, hypertension ranks 2nd out of the 10 most common diseases in hospital outpatients. Hypertension cannot be cured but can be controlled. Regular blood pressure checks are key in the management of the disease. Seeing this data, it is important to provide the right information through simple technical assistance to families, cadres, and the elderly to prevent and manage hypertension. The community service activity carried out is skill assistance to families and cadres in managing hypertension in the elderly in Ladang Baro Village, Meukek District, South Aceh Regency. The problems faced by partners include the lack of knowledge and skills of families and cadres in managing hypertension in the elderly. The purpose of this community service activity is to increase the knowledge and skills of the elderly, families, and cadres in managing hypertension. The problem solution offered in this community service is to provide education about hypertension and provide training to health cadres and selected communities on how to use digital tensimeters for blood pressure checks so that they can carry out appropriate management related to the disease they experience. The output of community service activities is expected to be articles submitted in accredited national journals or National Journals with ISSN and leaflets or booklets.